Analisis Pengaruh Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) dan Efisiensi Operasi (BOPO) terhadap Kinerja Keuangan Pasca Pandemi Covid-19 pada Beberapa Bank yang Tercatat di Bursa Efek Indonesia - Sitti Masyita; Sarmila (Insan Cita Bongaya Research Journal, 2024)
The purpose of this study is to test and analyze the effect of Loan to Deposit Ratio (LDR) on Financial Performance After the Covid-19 Pandemic in several banks listed on the Indonesia Stock Exchange. To test and analyze the effect of Capital Adequacy Ratio (CAR) on Post-Covid-19 Pandemic Financial Performance in several banks listed on the Indonesia St ock Exchange. To test and analyze the effect of Operating Efficiency (BOPO) on Financial Performance After the Covid-19 Pandemic in several banks listed on the Indonesia Stock Exchange. To achieve this goal, data collection techniques are used through documentation obtained through www.idx.co.id website. Data analysis techniques use descriptive analysis, classical assumption testing, multiple regression analysis and hypothesis testing. The findings of this study show that the Loan to Deposit Ratio (LDR) has a positive and significant effect on financial performance (ROA) after the Covid-19 in several banks listed on the IDX. The Capital Adequacy Ratio (CAR) has a positive and significant effect on financial performance (ROA) after the Covid-19 pandemic in several banks listed on the IDX. Operating expenses to operating income have a negative and significant effect on financial performance (ROA) after the Covid-19 pandemic in several banks listed on the IDX